Social Cohesion and Islamic Radicalization: Implications from the Uighur Insurgency - Tong Zhao (Journal of Strategic Security, 2010)
This article starts with a critical review of the current literature on the Islamic radicalization and Uighur insurgency in Xinjiang, pointing out that existing literature focuses too narrowly on certain aspects of the Uighur insurgency, and is insufficient to explain the causal mechanism of the insurgency and Islamic radicalization. Built upon historical evidence, this article uses sociological analysis to explore the structural changes in the Uighur community over the past decades, and demonstrates the importance and effectiveness of social cohesion theory in identifying the key causal variables which underlie and determine the course of Uighur insurgency and Islamic radicalization. The last section of the article offers policy implications on Islamic radicalization prevention at both international and domestic levels, and on how to reduce the negative impact of Islamic radicalism on national security and stability.